The Challenges in Developing Smart Tourism: A Literature Review - Teguh Iman Pribadi; Rusdin Tahir; Ayu Krishna Yuliawati (InfoTekJar : Jurnal Nasional Informatika dan Teknologi Jaringan, 2021)
Smart tourism is experiencing rapid development along with the information and communication technology (ICT) revolution. ICT has enabled companies engaged in tourism to be "smarter" in improving their performance and competitiveness. This study aims to determine the challenges in developing smart tourism. This study uses a literature review method. The data analyzed were obtained from several articles in accordance with the research theme. The selected articles are reputable articles that have been indexed by Scopus. After filtering the articles to be analyzed, 31 articles were selected according to the research theme raised. The results of this study indicate that apart from having many benefits, the development of smart tourism also has many challenges, such as, it requires a lot of money, many tourists and people are not aware of the new technology, reduced need for human resources, etc. These challenges must be considered by stakeholders so that the development of smart tourism can run smoothly and be accepted by the community.